Agricultural land expansion and deforestation in Malawi - Mindle, I.J.; Kowero, G.S.; Ngugi, D.; Luhanga, J. (2001)
The literature on deforestation in Malawi points to a number of causes, including high population in relation to available land, poverty, market and policy failures, drought, and the activity of structural adjustment policies. Agricultural statistics from Malawi indicate substantial increases in area under maize and tobacco between 1970-1994. Maize is the main single crop, occupying about 69 % of the cultivated land while tobacco is the main export and cash crops. A regression model was employed to highlight factors responsible for the expansion. The analysis suggests that the structural adjustment policies aimed at liberalization of tobacco production marketing of maize and tobacco, as well as increasing accessibility to foreign currency, had a positive and moderately significant influence on the expansion of the land area under maize but less on that under tobacco. given declining real producer prices for both crops, the driving force for the increasing area seems to be the desire by farmers to maintain their income from the sale of these two crops combined, rather than their prices. A household survey in three study areas chosen to cover a range in distance from the nearest town, confirmed significant increases in household land holdings is the recent past. Villagers living around the forest resources were identified as being key agents of deforestation, mainly through careless cutting of trees, opening up of gardens, grazing livestock and charcoal burning. These four activities constitute 84% of the reasons given by farmers for the increasing environmental degradation. The regression analyses provide some indication of factors associated with agricultural land expansion. The household study provide some insights on the agents of deforestation and to a limited extent how the increasing population is reacting to land famine.